Theoretical considerations on possibilities to develop adaptable centrifugal pumps as total artificial heart for individual body sizes - Köhne, Inge (Technium BioChemMed, 2021)
Thanks to the modern imaging techniques used in medical technology, it is now possible to scan a patient's chest without any problems. This should definitely be taken into account when designing a modern total artificial heart. With today's 3D construction programs it is possible to easily, and to the most part automatically, vary the construction of blood pumps. It is thus optimally adapted to the geometric circumstances of a patient.